The Tahlilan Tradition in Realizing Religious Moderation in Papan Rejo Village - Miswanto Miswanto; Mispani Mispani; Sunarto Sunarto (CV. Bimbingan Belajar Assyfa, 2026)
This research is motivated by the importance of understanding the role of local traditions in building religious moderation in multicultural societies. The tahlilan tradition, a religious practice of the Nahdlatul Ulama (NU) community to pray for the deceased, is often debated. However, in Papan Rejo Village, this tradition actually serves as a social glue among residents of different religions. This study aims to analyze the influence of the tahlilan tradition on community life, identify its positive values, and explore its role in realizing religious moderation. The research employed a qualitative approach with a phenomenological design. The research location was Papan Rejo Village, Abung Timur District, North Lampung Regency. Informants were selected using purposive sampling, including religious leaders, community leaders, and residents from various religious backgrounds. Data collection techniques included participant observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model. The results showed that the tahlilan tradition has become an integral part of community life, containing values of togetherness, mutual cooperation, friendship, and tolerance. This tradition plays an important role in realizing religious moderation through practices of mutual respect, interfaith participation, and conflict resolution based on local wisdom. Thus, tahlilan not only functions as a religious ritual but also as social capital to build harmony.